Brain Based Learning dalam Perspektif Guru di SD - Jayadi; Asep Supena (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to present information related to teacher perceptions regarding Brain Based Learning in teaching and learning activities at SDN K2 Karawang Regency which contains the implementation of brain based learning at SDN K2 Karawang Regency. Information was obtained from the results of interviews conducted with ten informants, namely six low class guardians and four high class guardians. The method used in this research is descriptive qualitative research method. The results of this study say that there are still many teachers who do not understand brain based learning so that learning often pays little attention to the concept of brain based learning. The impact experienced or felt by learning students only pursues the fulfillment of completing the subject matter (Target). Constraints experienced by teachers lack of understanding of brain based learning, so that in the learning process they pay less attention to the concept of brain based learning.